Browsing Behavior: Comparison between Real and Virtual Stores - Habibeche, Dhouka Oueldoubey (Journal of Research in Marketing (ISSN: 2292-9355), 2014)
This research aims to provide a comparison between two environments of shopping in the à point of view visitor behavior. Precisely, we speak of foraging behavior traditionally observed and analyzed in physical stores. This behavior is purely recreational and leisure purpose, pushing more and more decision makers to promote brands to benefit. Having a number of antecedents and consequences of this behavior pushes consumers to create a traffic attracted by certain variables store locations. We’ll compare these two worlds according to browsing behaviour.